2011
DOI: 10.1111/j.1471-0528.2011.03130.x
|View full text |Cite
|
Sign up to set email alerts
|

What women want. Women’s preferences for the management of low‐grade abnormal cervical screening tests: a systematic review

Abstract: Background If human papillomavirus (HPV) testing will replace cytology in primary cervical screening, the frequency of low-grade abnormal screening tests will double. Several available alternatives for the follow-up of low-grade abnormal screening tests have similar outcomes. In this situation, women's preferences have been proposed as a guide for management decisions.Objectives To determine women's preferences for the follow-up of low-grade cervical screening abnormalities.Search strategy Using Medical Subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 54 publications
0
17
0
1
Order By: Relevance
“…Preference studies related to cervical abnormalities largely focus on the management and surveillance of cervical dysplasia (8, 9). Limited research has examined preferences among patients with invasive cervical cancer (10, 11).…”
Section: Introductionmentioning
confidence: 99%
“…Preference studies related to cervical abnormalities largely focus on the management and surveillance of cervical dysplasia (8, 9). Limited research has examined preferences among patients with invasive cervical cancer (10, 11).…”
Section: Introductionmentioning
confidence: 99%
“…Although this statement may be correct based on the studies included in their review, we would like to emphasize that further studies are available that permit us to draw a more generalized conclusion. Based on our systematic review that identified 13 studies published between 1995 and 2010, 2 we observed that women may be more sensitive to whether they are managed immediately or observed for a longer period of time than to whether one or other test is used for their management. The majority of women facing imminent management for their positive screening test, arguably the most relevant situation for determining their preferences, preferred to have their diagnosis determined as soon as possible.…”
mentioning
confidence: 99%
“…The majority of women facing imminent management for their positive screening test, arguably the most relevant situation for determining their preferences, preferred to have their diagnosis determined as soon as possible. This was the case whether they were offered colposcopy (three studies), human papillomavirus (HPV) triage (one study), or even repeated cytology testing, but at shorter than standard intervals (one study) 2 . A further two studies that asked for women’s preferences after they had been managed for their own abnormality also showed a preference for immediate diagnostics in the form of colposcopy relative to observation with repeated cytology.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that treatment is not recommended for CIN 1 (cervical intraepithelial neoplasia grade 1), giving both the high rate of spontaneous regression as well as persistence after treatment [21]. However, even for low-grade abnormal cervical tests, women tend to prefer active management strategies; and it is very difficult to meet their expectations of optimal follow-up when HPV testing is used in primary screening [22].…”
mentioning
confidence: 99%